Implementasi Akad Muzara'ah pada Bank Syariah: Alternatif Akses Permodalan Sektor Pertanian - Ahmad Ajib Ridlwan (IQTISHODUNA: Jurnal Ekonomi Islam, 2016)
The purpose of writing this article is to know the law, muzara'ah cooperation model, applications such contract in the modern economy and how the opportunities and challenges in its implementation. Muzaraah in the agricultural sector is essential applied in Islamic banking as a superior product Indonesia Islamic bank as a real form of Islamic economic jurisprudence that benefit the community because the agricultural sector is a sector that can absorb large and very influential in food commodity and world economies. To realize the need for synergy between academia (universities), the association of Islamic banking, the association / community of farmers, agricultural ministries, NGOs, cooperatives sharia and sharia insurance deign to consider the creation of new products in Islamic banks that are specific to the agricultural sector given the low financing agriculture and the majority of farmers in the village with a little knowledge.